2017
DOI: 10.3390/e19020062
|View full text |Cite
|
Sign up to set email alerts
|

Complex and Fractional Dynamics

Abstract: Complex systems (CS) are pervasive in many areas, namely financial markets; highway transportation; telecommunication networks; world and country economies; social networks; immunological systems; living organisms; computational systems; and electrical and mechanical structures. CS are often composed of a large number of interconnected and interacting entities exhibiting much richer global scale dynamics than could be inferred from the properties and behavior of individual elements. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The test consists of creating a random dynamic process for the data and then studying how the scale of the stochastic process changes with time [67][68][69]. This test has been widely adopted as a suitable tool to confirm the chaotic behavior in fractional-order dynamical systems [26,33,40] because it is binary (minimizing issues of distinguishing small positive numbers from zero); the nature of the vector field, as well as its dimensionality, does not pose practical limitations; and it does not suffer from the difficulties associated with phase space reconstruction.…”
Section: Test 0-1 For Chaosmentioning
confidence: 99%
See 1 more Smart Citation
“…The test consists of creating a random dynamic process for the data and then studying how the scale of the stochastic process changes with time [67][68][69]. This test has been widely adopted as a suitable tool to confirm the chaotic behavior in fractional-order dynamical systems [26,33,40] because it is binary (minimizing issues of distinguishing small positive numbers from zero); the nature of the vector field, as well as its dimensionality, does not pose practical limitations; and it does not suffer from the difficulties associated with phase space reconstruction.…”
Section: Test 0-1 For Chaosmentioning
confidence: 99%
“…In recent years, fractional calculus has received much attention due to fractional derivatives providing more accurate models than their integer-order counterparts. Many examples have been found in different interdisciplinary fields [25], ranging from the description of viscoelastic anomalous diffusion in complex liquids, D-decomposition technique for control problems, chaotic systems; to macroeconomic models with dynamic memory, forecast of the trend of complex systems, and so on [26][27][28][29][30][31][32][33][34]. Those works have demonstrated that fractional derivatives provide an excellent approach to describing the memory and hereditary properties of real physical phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamical networks, including brain networks 1 , quantum networks 2 , financial networks 3 , gene networks 4 , protein networks 5 , cyber-physical system networks 6 (e.g. power networks 2 , healthcare networks 7 ), social networks 8 , and physiological networks 9 , exhibit not only an intricate set of higher-order interactions but also exhibit distinct long-term memory dynamics where both the recent and more distant past states influence the state's evolution. Regulating these long-term memory dynamical networks in a timely fashion becomes critical to avoid a fullblown catastrophe.…”
mentioning
confidence: 99%